WOMAN AND WOMANHOOD IN “THE WOMAN WARRIOR” BY MAXINE HONG KINGSTON - Mamatqulova Kumushoy; Dilnoza Ruzmatova (American Journals, 2022)
‘She’ is a pronoun which designates female gender in English language. The study of the female role becomes pivotal when it comes to diaspora which is an automatic generated notification due to cultural clash. The feeling of diaspora unveils interesting episodes of cultural juxtaposition and conflicts. Women are considered to be an integral part of any culture. She is the bearer of culture and she is the representative of culture. Woman and womanhood is a very actual theme in any society. Thanks to feminist writers who published a lot of fictions and non-fictions due to make aware of women’s rights and feelings to the world. Especially in diaspora literature we can see a number of writers contributed for increasing the role of women. The concept of diaspora is associated with migration and dispersal. The term, in common parlance, signifies any people living outside their homeland.